2009
DOI: 10.5897/ajpp10.309
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the medical benefit in the folkloric use of Bryophyllum Pinnatum leaf among the Igbos of Nigeria for the treatment of hypertension

Abstract: The effects of aqueous leaf extract of Bryophyllum pinnatum on the blood pressure of anaesthetized cats, as well as on the liver and kidney status of the rabbit were investigated in this study. The results revealed that, the extract produced a small fall in the blood pressure of the anaesthetized cat and also reduced the effect of adrenaline-induced elevation of blood pressure. In rabbits, biochemical analysis of serum was carried out; urea and creatinine were used as tests of its effect on the renal function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
0
29
0
1
Order By: Relevance
“…It was concluded that the pharmacological basis for the use of K. pinnata among the Igbos of Nigeria to lower blood pressure was established by this study. However, the facts that the reduction in blood pressure produced is slight and the K. pinnata leaf extract is potentially organotoxic which negates its use as a blood pressure lowering agent (Ghasi et al, 2011).…”
Section: Antihypertensive Activitymentioning
confidence: 99%
“…It was concluded that the pharmacological basis for the use of K. pinnata among the Igbos of Nigeria to lower blood pressure was established by this study. However, the facts that the reduction in blood pressure produced is slight and the K. pinnata leaf extract is potentially organotoxic which negates its use as a blood pressure lowering agent (Ghasi et al, 2011).…”
Section: Antihypertensive Activitymentioning
confidence: 99%
“…It is commonly known as Life plant, Air plant, Love plant, and Goethe plant. B. pinnatum has been widely used in traditional medicine, especially in Madagascar, Indonesia, India, Nigeria, Trinidad and Tobago where the leaves have been utilized to treat jaundice [1], skin diseases, urinary problems, hypertension, and for its cooling properties in topical use [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiodepression and vasodilation may be associated with the antihypertensive effect of the plant, says Ojewole (2002). Ghasi et al, (2011) observed that the fall in adrenaline-induced increase in blood pressure of cats was due to the administration of aqueous extract of the plant. The blood pressure decreased with increasing dose of the extract.…”
Section: Antihypertensive Activitymentioning
confidence: 99%